Effects of transmitted solar irradiance on predicted mean vote in perimeter zone of west-facing lecture rooms with unprotected glazed windows - Rusli, Ijhar Hidayat (2011)
One of the methods employed in creating a sustainable built environment is the maximisation in usage of day lighting through glazed walls. From an energy efficiency standpoint, such measures have been proven beneficial through the reduction in energy demand in several aspects. The same, however, cannot be said regarding the thermal comfort levels of occupants seated nearby the glazed walls, affected by the transmitted solar irradiance wherein only a limited number of studies have been conducted on the particular subject matter. To make matters worse, buildings and their enclosures cannot always be built with their orientation as the number one priority and as a result a significant amount of heat gain to the enclosure is almost imminent. This dissertation presents a semi-empirical study of the shift in thermal comfort conditions, expressed in terms of the predicted mean vote (PMV), expected to be inflicted upon an occupant hypothetically seated nearby a glazed wall and subjected to transmitted solar irradiance within the context of the hot-humid tropical climate. The sun’s geometrical positioning in relation to the occupant’s was considered for different hours of a day throughout a year. The objective of the study is to determine the combined effects of 1) the intensity of the solar irradiance transmitted through the glazed wall and 2) the geometrical positioning of its source on the thermal comfort levels of the occupant. Measurements of the intensity and temporal distribution of the irradiance transmitted through the glazed wall were conducted using a pyranometer connected to a data acquisitioning system. The shift in radiation-induced thermal comfort conditions were quantified using a mathematical model cited by the literature. Statistics of the intensity of irradiance transmitted through the glazed wall have been determined and discussed. Inter- and intra-month comparisons were conducted of the thermal comfort levels of the occupant subjected to the irradiance for different hours of the day. It was determined that peak values of the irradiance transmitted through the windows averaged between 40 – 50 W/m2 occurring between the hours of 15:00 – 16:00 h local time. Throughout the year, the sun-occupant geometrical relation was determined to be maximised in the months of June and July; for any given day it is maximised towards the end of the day. Coupling of these two findings showed that the predicted mean vote would see an increase between 0.1 – 0.5 units on the 7-point comfort scale occurring between 16:00 – 17:00 h local time. Objectively, under the tested circumstances, thermal comfort could be maintained within acceptable limits